ATTITUDE OF TEACHERS TOWARDS IMPLEMENTATION OF CURRICULUM IN ISLAMIYYAH SCHOOLS WITHIN KADUNA METROPOLIS - Aliyu, Mamman (Sokoto Educational Review, 2020)
The objective of the paper is to examine the attitude of teachers towards implementation of curriculum in the Islamiyyah primary schools within Kaduna Metropolis. The study reveals that the teachers’ attitude towards curriculum implementation is favourable. In the related areas of teachers’ motivation and conduciveness of learning atmosphere, the study discovered that the situation is not favourable. To improve the situation, the study recommended the provision of adequate learning facilities like classrooms, furniture, fittings etc by the proprietors of the schools.